DAMPAK EKONOMI DIGITAL BAGI UMKM (Studi Kasus Usaha SPA Di Kota Pekanbaru) - Rahim Abibur; Mardiana Mardiana; Zuryani Hilmah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research was conducted to identify the benefits of the digital economy and its impact on SPA in the Pekanbaru City area. This research is a quantitative descriptive study, which combines questionnaires, in-depth interviews and observations of SPA as well as the digital economic media used. Subjects were selected by purposive sampling. The results showed that the most widely used digital economic media were shopee, instagram, and whatsapp. Most of the SPA use the digital economy to conduct promotions, sales and as a medium of information. From this research, it can be seen that the digital economy can increase revenue and the number of customers.Keywords: SPA, Digital Economy, Income, Customers